CRUSTACEAN TAXONOMY- A SOLUTION FOR CONSERVING ITS BIODIVERSITY IN INDIA - SRUTHI, H.; THIRUNAVUKKARASU, N. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Crustaceans play major role in ecological enhancement and improvement in economic value of Indian fisheries. Due to over exploitation and constant demand, various species of crustaceans in wild had gradually decreased from 1996 to 2016 all around India which lead to great ecological imbalance. According to IUCN Red Data List 2019 about 27% of selected crustaceans are in threatened category globally whereas in India about 1.54% of crustaceans are in threatened category and about 37.5% of crustacean data are deficient. Out of 17.5% of global endemic crustacean species about 5.9% of endemic crustaceans are found in India but the worst scenario is the population of these species too has deteriorated due to over exploitation. This will lead to enormous loss to biodiversity by not finding any clue about unexplored extinct species. At this juncture, taxonomy plays key role in assessment of species in the wild and employs in assisting conservative programs for documenting biodiversity. It also provides checklist for in-situ conservation of those species which in turn help in elevating the economic development of crustacean fisheries. It will also help in creating awareness on the alarming condition of biodiversity loss. This article explains the exact scenario of crustacean population in India and highlights the role of taxonomy in its conservation.